A Behavioral Genetic Study of Intrapersonal and Interpersonal Dimensions of Narcissism - Luo, Yu L. L. (Public Library of Science, 2014)
Narcissism, characterized by grandiose self-image and entitled feelings to others, has been increasingly prevalent in the past decades. This study examined genetic and environmental bases of two dimensions of narcissism: intrapersonal grandiosity and interpersonal entitlement. A total of 304 pairs of twins from Beijing, China completed the Narcissistic Grandiosity Scale and the Psychological Entitlement Scale. Both grandiosity (23%) and entitlement (35%) were found to be moderately heritable, while simultaneously showing considerable non-shared environmental influences. Moreover, the genetic and environmental influences on the two dimensions were mostly unique (92–93%), with few genetic and environmental effects in common (7–8%). The two dimensions of narcissism, intrapersonal grandiosity and interpersonal entitlement, are heritable and largely independent of each other in terms of their genetic and environmental sources. These findings extend our understanding of the heritability of narcissism on the one hand. On the other hand, the study demonstrates the rationale for distinguishing between intrapersonal and interpersonal dimensions of narcissism, and possibly personality in general as well.